ALKBH5 alleviates lower extremity arteriosclerosis by regulating ITGB1 demethylation and influencing macrophage polarization - Zeyu Guan; Xiaogao Wang; Chao Xu; Ran Lu (Heliyon)
Objective: M6A methylation-regulated macrophages play an important role in the occurrence and development of arteriosclerosis. However, their role in lower extremity arteriosclerosis remains unclear. Therefore, this study aims to explore the key factors that regulate arteriosclerosis methylation in the lower extremities and the mechanism by which they affect arteriosclerosis by influencing macrophage polarization. Methods: The m6A methylation levels in peripheral blood mononuclear cells (PBMCs) of patients with lower extremity atherosclerosis was investigated using the Dot blot method. Additionally, the expression levels of RNA methyltransferases and demethylases were examined using ELISA and Western blotting. Inflammatory macrophages were established using RAW264.7 cells stimulated with LPS (100 ng/mL), and the expression of ALKBH5 and ITGB1 was evaluated using Western blotting. Immunofluorescence staining was conducted to assess the expression of M1 macrophage markers (F4/80+CD86) and M2 macrophage markers (F4/80+CD206) in renal tissue. ELISA was employed to measure the levels of cytokines (IL-6, IL-1β, TNF-a, IL-10, and TGF-β) and plasma lipid levels in mice. An atherosclerosis model was established in ApoE−/− mice through balloon pull surgery and high-fat feeding. Oil Red O staining and hematoxylin and eosin (HE) staining were performed to measure the area of atherosclerotic plaques and the size of the necrotic core in mouse femoral artery, respectively. Additionally, Starbase2.0 was used for downstream target gene prediction of ALKBH5. The half-life of ITGB1 was evaluated using RT-qPCR. Results: The m6A methylation levels were significantly increased in PBMCs of patients with lower extremity atherosclerosis. Among them, the expression of the RNA demethylase ALKBH5 was the lowest in PBMCs of patients with lower extremity atherosclerosis. Further analysis revealed that ALKBH5 can alleviate the progression of lower extremity atherosclerosis and promote the polarization of M2 macrophages. ALKBH5 can reduce the stability of ITGB1 through demethylation. Mechanistically, ALKBH5 influences macrophage polarization and mitigates lower extremity atherosclerosis by affecting the demethylation of ITGB1. Conclusion: ALKBH5 promotes M2 macrophage polarization and alleviates lower extremity atherosclerosis by regulating the demethylation of ITGB1. A deeper understanding of this process not only helps elucidate the molecular mechanisms of atherosclerosis but also provides possibilities for the development of new therapeutic strategies.